Najaf Poetry and Criticism of Political Reality - Abdul, Shahd Azim; Enooz, Sabah Abbas (Journal of Ecohumanism, 2024)
The aim of the research is to identify Najaf poetry and criticize the political reality of the period from (1900-1950). The importance of the research comes through knowing the role of Najaf poets in criticizing the bitter political reality that Iraq experienced in general and the city of Najaf in particular, and what political life in the city has become under the Ottoman and British occupations. The poets of Najaf expressed their criticism of the bitter political reality in that period in their poetry, literary writings, and their defense of the sanctities and fixed national values. The researcher followed the descriptive analytical approach to suit the current research to reach the most important results that the current research has reached.